Phylum Kinorhyncha. In: Zhang, Z.-Q. (Ed.) Animal Biodiversity: An Outline of Higher-level Classification and Survey of Taxonomic Richness (Addenda 2013) - Sørensen, Martin V. (Zootaxa, 2013)
The phylum Kinorhyncha includes 196 described species, distributed on 21 (soon 22) genera, and nine families. Two genera are currently not assigned to any family. The families are distributed on two orders, Cyclorhagida and Homalorhagida. Currently, kinorhynch classification does not reflect actual relationships revealed as a result of numerical phylogenetic analyses, but such studies are currently being carried out, and a revision of the kinorhynch classification is expected within a short time.